Osteosarcoma immune microenvironment: cellular struggle and novel therapeutic insights - Zhang, Yi; Jiang, Shasha; Lv, Jing; Feng, Wei; Yu, Yan; Zhao, Heping (Frontiers in Immunology, 2025)
Recent advances in immunotherapy have shown remarkable success across multiple solid tumor types, revitalizing interest in immune-modulating strategies for osteosarcoma (OS). Within the complex tumor microenvironment (TME), immune cells exhibit dual regulatory roles-exerting critical regulatory influences on both tumorigenesis and disease progression while simultaneously serving as therapeutic targets. Particularly in OS, the dynamic interplay between malignant cells and the unique bone microenvironment manifests through intricate immune cell-mediated crosstalk. This comprehensive review analyzes the paradoxical roles of immune cell subsets in OS pathophysiology, detailing their tumor-promoting versus tumor-suppressing functions. Furthermore, we systematically evaluate recent progress in immune cell-targeted therapeutic approaches, including adoptive cell therapies and macrophage reprogramming strategies. The review encompasses current clinical applications and emerging preclinical innovations, providing valuable insights for optimizing immunotherapeutic approaches in OS management.